Component-wise Biomass Models for Trees: a Non-harvest Technique - Tiwari, A. K. (Indian Forester, 1992)
The present study deals with the generation of the technique for component-wise species biomass estimation models. The technique emphasises the use of sampling of tree components, rather than felling of the complete tree. A series of models was developed for biomass estimation of various tree components. The biomass of different components of various trees individuals was related with the cbh through allometric equations. The results obtained through present models compared well with the estimates obtained through harvest method.